ANALISIS PENGARUH ESG DAN GCG TERHADAP VALUE RELEVANCE DENGAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI - Raditya Dimas Supriyanto; Nur Cahyonowati (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure and Good Corporate Governance (GCG) implementation on corporate Value Relevance, as well as to examine the role of firm size as a moderating variable in these relationships. The background of this research is based on the inconsistency of previous research findings and the importance of non-financial information for investors, particularly in the mining sector which carries high environmental and social risks as well as a need for governance transparency. This study employs a quantitative approach with a population of mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 period. The sampling technique used was purposive sampling, resulting in 26 companies as samples with a total of 78 observations. Data were analyzed using Moderated Regression Analysis (MRA) with the Random Effect Model (REM) estimation method using EViews 12 software. The independent variable ESG is measured using GRI standards, GCG is measured using ACGS guidelines, while the dependent variable value relevance is proxied by Tobin’s Q, and firm size is proxied by the Natural Logarithm of Total Assets. The results of this study indicate that ESG disclosure has no significant effect on value relevance, suggesting that investors tend to respond neutrally to ESG information. GCG implementation was found to have a significant negative effect on value relevance, indicating a market perception regarding over-compliance costs. Regarding the moderating variable, the test results prove that firm size is unable to moderate the relationship between ESG and value relevance. However, firm size is proven to positively moderate (strengthen) the effect of GCG on value relevance. These findings imply that good corporate governance is only effective in increasing firm value if implemented by large-scale companies that have sufficient resources and high visibility.